Strobilanthes crispus antibacterial against Aggregatibacter actinomycetecomitans - Arum Suproborini; Mochamad Soeprijadi Djoko Laksana; Widia Puspita (Cita Konsultindo Research Center, 2023)
Aggregatibacter actinomycetecomitans is a bacteria that causes periodontitis. One of the plants that has antibiotic properties is the shard (Strobilanthes crispus). This study aims to determine the effect of the ethanol extract of Strobilanthes crispus leaves on the growth of Aggregatibacter actinomycetecomitans bacteria. This research is a quantitative study using the experimental laboratory method. The research stages included the selection of Strobilanthes crispus leaves as herbal ingredients, manufacture of leaf simplicia, ethanol extraction of Strobilanthes crispus leaves using the maceration method, and testing the effect of ethanol extract of Strobilanthes crispus leaves on the growth of Aggregatibacter actinomycetemcomitans bacteria using the well diffusion method with three each. Repeat times, measurement of inhibition zone diameter, and MIC determination with chlorhexidin 0.2% positive control. The measurement results of the average diameter of the inhibition zone of Strobilanthes crispus extract against Aggregatibacter actinomycetecomitans bacteria at a concentration of 25%, 50%, 75% were 10 mm, respectively, and at a concentration of 100% was 16.67 mm. The mean of inhibition zone for positive control against Aggregatibacter actinomycetecomitans bacteria was 16.33 mm. Based on the inhibition zone diameter, the MIC against Aggregatibacter actinomycetecomitans was 10 mm, namely at a concentration of 25%. Strobilanthes crispus extract is effective for Aggregatibacter actinomycetecomitans bacteria.